Ad-Dakhil dalam Tafsir Al-Azhar : Studi Kritis terhadap Riwayat Israiliyyat pada Tafsir Ayat-Ayat Kisah - M. Aufa; Ziyad Ulhaq; Ahmad Syukron (Lembaga Pengembangan Kinerja Dosen, 2026)
This study examines Ad-Dakhil in Tafsir Al-Azhar by Buya Hamka, focusing on Israiliyyat narrations found in the interpretation of Qur’anic narrative verses in Juz 1–10. The research is motivated by the position of Israiliyyat as a form of infiltration (ad-dakhil) in Qur’anic exegesis that may affect the objectivity of interpretation, particularly in contemporary tafsir works. This study aims to identify the distribution of Israiliyyat narrations, classify their thematic patterns, and determine the status of each narration based on the critical framework of ad-dakhil fi at-tafsir. This research employs a qualitative library-based approach. The primary source is Tafsir Al-Azhar by Buya Hamka (Gema Insani, 2017), supported by classical and contemporary tafsir literature as well as scholarly works on Israiliyyat. Data were analyzed using the theory of ad-dakhil fi at-tafsir, classifying narrations into three categories: accepted (maqbul), rejected (mardud), and suspended (tawaqquf). The findings reveal seventeen Israiliyyat narrations scattered throughout Juz 1–10, originating from the Old Testament, the New Testament, Wahb bin Munabbih, ‘Abdullah ibn Mas‘ud, and Tafsir Ibn Kathir. These narrations fall into nine major themes, including the creation and origin of humanity, the story of Prophet Adam and his descendants, Prophet Ibrahim, Prophet Ya‘qub, Prophet Musa and Bani Israil, Prophet Sulaiman, Prophet Zakariya, Prophet ‘Isa and his people, as well as accounts of previous nations. Of these seventeen narrations, eleven are classified as rejected (mardud), five as tawaqquf, and one as accepted (maqbul). These results emphasize the necessity of critical engagement with Israiliyyat narrations in tafsir literature to preserve the integrity of Qur’anic interpretation.